In physics, the Landé g-factor is a particular example of a g-factor, namely for an electron with both spin and orbital angular momenta. It is named after Alfred Landé, who first described it in 1921.[1]
In atomic physics, the Landé g-factor is a multiplicative term appearing in the expression for the energy levels of an atom in a weak magnetic field. The quantum states of electrons in atomic orbitals are normally degenerate in energy, with these degenerate states all sharing the same angular momentum. When the atom is placed in a weak magnetic field, however, the degeneracy is lifted.
The factor comes about during the calculation of the first-order perturbation in the energy of an atom when a weak uniform magnetic field (that is, weak in comparison to the system's internal magnetic field) is applied to the system. Formally we can write the factor as,[2]
gJ=
g | ||||
|
+g | ||||
|
.
The orbital
gL
gS=2
gJ(gL=1,gS=2)=1+
J(J+1)+S(S+1)-L(L+1) | |
2J(J+1) |
.
Here, J is the total electronic angular momentum, L is the orbital angular momentum, and S is the spin angular momentum. Because
S=1/2
S(S+1)
S=0
gJ=1
L=0
gJ=2
If we wish to know the g-factor for an atom with total atomic angular momentum
\vec{F}=\vec{I}+\vec{J}
F=J+I,J+I-1,...,|J-I|
\begin{align} gF&=
g | ||||
|
+g | ||||
|
F(F+1)+I(I+1)-J(J+1) | |
2F(F+1) |
\\ & ≈
g | ||||
|
\end{align}
Here
\muB
\muN
\muN
\muB
The following working is a common derivation.[3] [4]
Both orbital angular momentum and spin angular momentum of electron contribute to the magnetic moment. In particular, each of them alone contributes to the magnetic moment by the following form
\vec\muL=-\vecLgL\mu\rm/\hbar
\vec\muS=-\vecSgS\mu\rm/\hbar
\vec\muJ=\vec\muL+\vec\muS
gL=1
gS ≈ 2
gS
\vec\muJ
\vecJ=\vecL+\vecS
\vecJ
\langleJ,Jz|\vec\muJ|J,J'z\rangle=-gJ\mu\rm\langleJ,Jz|\vecJ|J,J'z\rangle
\langleJ,Jz|\vec\muJ|J,J'z\rangle ⋅ \langleJ,J'z|\vecJ|J,Jz\rangle=-gJ\mu\rm\langleJ,Jz|\vecJ|J,J'z\rangle ⋅ \langleJ,J'z|\vecJ|J,Jz\rangle
\sum | |
J'z |
\langleJ,Jz|\vec\muJ|J,J'z\rangle ⋅ \langleJ,J'z|\vecJ|J,Jz\rangle=
-\sum | |
J'z |
gJ\mu\rm\langleJ,Jz|\vecJ|J,J'z\rangle ⋅ \langleJ,J'z|\vecJ|J,Jz\rangle
\langleJ,Jz|\vec\muJ ⋅ \vecJ|J,Jz\rangle=-gJ\mu\rm\langleJ,Jz|\vecJ ⋅ \vecJ|J,Jz\rangle=-gJ\mu\rm \hbar2J(J+1)
\begin{align} gJ\langleJ,Jz|\vecJ ⋅ \vecJ|J,Jz\rangle&=\langleJ,Jz|gL{{\vecL} ⋅ {\vecJ}}+gS{{\vecS} ⋅ {\vecJ}}|J,Jz\rangle\\ &=\langleJ,Jz|gL{(\vec
| ||||
L |
(\vecJ2-\vecL2-\vec
2))}+g | |
S | |
S |
{(\vec
| ||||
S |
(\vecJ2-\vecL2-\vec
2))}|J,J | |
S | |
z\rangle |
\\ &=
gL\hbar2 | |
2 |
(J(J+1)+L(L+1)-S(S+1))+
gS\hbar2 | |
2 |
(J(J+1)-L(L+1)+S(S+1))\\ gJ&=gL
J(J+1)+L(L+1)-S(S+1) | |
{2J(J+1) |